Greater sage‐grouse in Montana: Mapping archetype viewpoints across stakeholder groups using Q methodology - D'jeane T. Peters; Lucas Ward (Wildlife Society Bulletin)
ABSTRACT We conducted a Q‐method‐based study to examine patterns of agreement and disagreement across stakeholder groups regarding greater sage‐grouse (Centrocercus urophasianus) management in Montana, USA, between 2010 and 2014. Tested groups consisted of government natural resource managers, advocacy groups, landowners, and concerned citizens. We asked 49 representatives of 14 different stakeholder agencies to complete a Q‐method assessment of their viewpoints on greater sage‐grouse management in Montana. We identified the substantively different ways that stakeholders organized their views on 2 issues: 1) What is the condition of greater sage‐grouse in Montana? (i.e., the problem); and 2) What should be done about it? (i.e., the solution). We identified 3 “archetypes” (or factors in Q‐method terminology): Limit Development, Local Governance, and Limit Regulation—each of which prioritized a different set of management values. We found that viewpoints toward climate change and predators were issues that created divisions among archetypes regarding sources of greater sage‐grouse mortality, whereas the issues of sod‐busting (breaking up new ground for cultivation) and concerns for the economic impacts of listing as an endangered species could be starting points for building consensus among stakeholder groups. Not only did Q methodology reveal the issues that divided the 3 archetypes and those issues that served as common ground, it also identified stakeholders whose viewpoints made them well‐suited to act as agents of consensus or translators during contentious decision‐making processes. © 2017 The Wildlife Society.